Potensi Antibakteri Ekstrak Daun Mentimun (Cucumis sativus L.) dan Madu: Tinjauan Pustaka - Ryan Agustin Purba; Soraya Rahmanisa; Gigih Setiawan; Evi Kurniawaty (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Bacterial infections remain a major global health concern, particularly because antimicrobial resistance continues to compromise the effectiveness of conventional antibiotics and increase the demand for alternative therapeutic agents. Natural products, including cucumber (Cucumis sativus L.) leaves and honey, have attracted increasing attention due to their diverse bioactive compounds with antibacterial properties. This study aimed to review recent evidence regarding the antibacterial potential of cucumber leaf extract and honey. A narrative literature review was conducted using publications indexed in Google Scholar, PubMed, ScienceDirect, Scopus, and SpringerLink from 2021–2026. Articles meeting predefined inclusion and exclusion criteria were analyzed descriptively and comparatively. The synthesis of ten eligible studies demonstrated that cucumber leaf extract exhibits antibacterial activity through phytochemicals, green-synthesized titanium dioxide nanoparticles, and endophytic microorganisms, whereas honey provides broad-spectrum antibacterial effects influenced by its botanical origin and physicochemical characteristics. Current evidence also suggests potential complementary mechanisms between both natural products, although direct combination studies remain limited. Further standardized in vivo investigations and clinical trials are required to validate their efficacy and safety for future therapeutic applications.